(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
The particular article argues that derivation can be approached via a usage-based cognitive model, proclaiming that conceptual processes motivate grammatical phenomena, as argued by, Brdar (2007), Langacker (2009), Radden and Kövecses (1999) and Ruiz de Mendoza and Galera-Masegosa (2014). Evidence is provided by means of the examination of Modern Greek verbs which delineate how derivation, and in particular suffixation, works. In other words, the study comprises a limited etymological research over two productive and frequent verb suffixes in Greek –ízo and –óno. The attested verbs – σκοτίζω [skot-ίzo] versus σκοτώνω [skotόno], φορτίζω [fortίzo] versus φορτώνω [fortόno], ζυγίζω [ziγίzo] versus ζυγώνω [ziγόno], κεντρίζω [kendrίzo] versus κεντρώνω [kendrόno], and θυμίζω [θimίzo] versus θυμώνω [θimόno] share the same root; however, the suffixes that are attached to them, namely, -izo and -όno diversify the meaning leading to different scenarios, which occasionally bear a figurative meaning or they arose due to metonymic or metaphoric mappings.